Taking Data Literacy to the Streets: Critical Pedagogy in the Public Sphere. (February 2020) - Markham, Annette N.
This article describes an ongoing series of public arts–based experiments that build critical curiosity and develop data literacy via self-reflexive public interventions. Examined through the lens of remix methodology the Museum of Random Memory exemplifies a form of collective–reflexive meta-analysis whereby interdisciplinary researchers generate immediate social change and build better questions for future public engagement. The experiments help people critically analyze their own social lives and well being in cultural environments of growing datafication and automated (artificial intelligence [AI]-driven) decision-making. Reflexivity, bricolage, and critical pedagogy are emphasized as approaches for responding to changing needs in the public sphere that also build more robust interdisciplinary academic teams.